Defaults and Donations: Evidence from a Field Experiment - Steffen Altmann; Armin Falk; Paul Heidhues; Rajshri Jayaraman (Institute for the Study of Labor (IZA), 2014)
We study how website defaults affect consumer behavior in the domain of charitable giving. In a field experiment that was conducted on a large platform for making charitable donations over the web, we exogenously vary the default options in two distinct choice dimensions. The first pertains to the primary donation decision, namely, how much to contribute to the charitable cause. The second relates to an "add-on" decision of how much to contribute to supporting the online platform itself. We find a strong impact of defaults on individual behavior: in each of our treatments, the modal positive contributions in both choice dimensions invariably correspond to the specified default amounts. Defaults, nevertheless, have no impact on aggregate donations. This is because defaults in the donation domain induce some people to donate more and others to donate less than they otherwise would have. In contrast, higher defaults in the secondary choice dimension unambiguously induce higher contributions to the online platform.
Keywords: C93; D03; D64; 330; default options; charitable giving; online platforms; field experiment